Metode Pelatihan Tari pada Pengembangan Diri di SMP Negeri 40 Padang - Fanny Syafitri; Afifah Asriati (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This study aims to identify and describe the dance training model for dance self-development at SMP Negeri 40 Padang. This type of research is a qualitative research with descriptive method. Research instruments, researchers themselves and assisted with supporting instruments such as laptops, stationery and cameras. Observation and documentation data collection techniques. The steps to analyze the data are data reduction, data presentation and conclusion. The results showed that the peer tutoring method, the demonstration method, and the dance training group method for the self-development of the art of dance at SMP N 40 Padang had produced student activities and skills well. This is evident from the results of observing student activity from the first meeting to the last meeting. There was an increase in student activity from the first meeting to the fourth meeting. Likewise with students' skills in performing motion in terms of technique and memorization of motion.